The Consumers' Choice of Purchasing Location and the Preferences for Beef in Yogyakarta - Wankar, Tian Jihadhan; Morales, E.; Griffith, G.; Agus, A.; Guntoro, B. (Universitas Bengkulu, 2023)
This study aims to analyze the consumer preferences about choosing a place to buy beef and beef attribute product influence in buying decision of consumers in Yogyakarta. There were 300 beef consumers selected near traditional markets, butcher or meat shops, supermarkets, restaurants and food stalls for the survey using the questionnaire. The data were analyzed descriptively and used the chi-square test to evaluate the relationship between demographic characteristics and the consumers' choice of place when buying beef in Yogyakarta. The study reveals that most respondents buy beef at butcher or meat shops, followed by traditional markets and supermarkets. Consumers consider price, top quality of beef, the freshness of the product, shopping convenience and friends with sellers as the top five reasons when they choose a place to buy beef. Further, there is no correlation between demographic aspects with consumer preferences in choosing a place to buy beef. Finally, the beef attributes consumers consider when buying beef are the halal slaughtering method, bright red colour, quality assured and beef cuts.